FIRST REPORT ON THE UPPERMOST PERMIAN OSTRACODS FROM THE MASORE SECTION (EXTERNAL DINARIDES), SLOVENIA (Rivista italiana di Paleontologia e Stratigrafia, 2024)
The ostracod assemblages from the Upper Permian and Permian-Triassic transitional strata of the Masore section in the External Dinarides (Slovenia) were studied. Altogether 13 genera and 20 species of the orders Palaeocopida, Platycopida and Podocopida are identified and illustrated. All recovered ostracods belong to shallow marine taxa. The older fauna from the uppermost Permian and the younger fauna from the Permian-Triassic boundary strata are distinguished. The obtained fauna from the Permian Bellerophon Formation corresponds to the “benthonic ostracod Eifelian Mega-assemblage” occupying the shelf sea floors. This study presents the first report of ostracod faunas from the uppermost Permian and Permian-Triassic boundary interval of Slovenia. The recovered ostracod fauna display a distinct faunal change and yield important paleobiogeographic implications as it reveals similarity with stratigraphical equivalent faunas from some other neighboring localities in the western Paleotethys, such as Bulla in Italy, Komirić in Serbia, and the Bükk Mountains in Hungary.